Genome Functional Analysis of the Psychrotrophic Lignin-Degrading Bacterium Arthrobacter sp. C2 and the Role of DyP in Catalyzing Lignin Degradation - Jiang, Cheng; Yan, Haohao; Shen, Xiaohui; Zhang, Yuting; Wang, Yue; Sun, Shanshan; Jiang, Hanyi; Zang, Hailian; Zhao, Xinyue; Hou, Ning; Li, Ziwei; Wang, Liwen; et al. (Frontiers in Microbiology, 2022)
In the cold regions of China, lignin-rich corn straw accumulates at high levels due to low temperatures. The application of psychrotrophic lignin-degrading bacteria should be an effective means of overcoming the low-temperature limit for lignin degradation and promoting the utilization of corn straw. However, this application is limited by the lack of suitable strains for decomposition of lignin; furthermore, the metabolic mechanism of psychrotrophic lignin-degrading bacteria is unclear. Here, the whole genome of the psychrotrophic lignin-degrading bacterium Arthrobacter sp. C2, isolated in our previous work, was sequenced. Comparative genomics revealed that C2 contained unique genes related to lignin degradation and low-temperature adaptability. DyP may participate in lignin degradation and may be a cold-adapted enzyme. Moreover, DyP was proven to catalyze lignin Cα-Cβ bond cleavage. Deletion and complementation of the DyP gene verified its ability to catalyze the first-step reaction of lignin degradation. Comparative transcriptomic analysis revealed that the transcriptional expression of the DyP gene was upregulated, and the genetic compensation mechanism allowed C2ΔDyP to degrade lignin, which provided novel insights into the survival strategy of the psychrotrophic mutant strain C2ΔdyP. This study improved our understanding of the metabolic mechanism of psychrotrophic lignin-degrading bacteria and provided potential application options for energy-saving production using cold-adapted lignin-degrading enzymes.